WOMEN`S ADDRESS FORMS VARIATION IN RUSSIAN - Ziyadullayeva Mokhira (Galaxy International Interdisciplinary Research Journal, 2023)
In this article information is given about the specific features of addressing and the stages of development. This article illustrates about how to address among women in Russian.